Evaluating the CNS Activity of Methanolic Extract of Anogeissus latifolia Leaves on Various Experimental Rat Models - K. Hemamalini; K. Veeresh; M. Vijusha; N. Pruthvi Raju; A. Rajani (Novel Aspects on Pharmaceutical Research Vol. 2, 2023)
The purpose of this study was to evaluate the muscle coordination and anxiolytic properties of methanolic extracts of Anogeissus latifolia (combretaceae) in mice utilizing varied models of using mice. In the research, diazepam served as the standard medication. The extracts were given orally at two doses of 300 mg and 400 mg/kg. The current study’s findings suggest that Anogeissus latifola leaf methanolic extract is efficient in causing a significant protection against muscle coordination and anxiolytic effects, as demonstrated by several CNS models compared to controls. It is well known that the Methanolic extract of leaves of Anogeissus latifolia, which is proposed as its hypotensive principle. This investigation proved the plant’s muscle coordination and anxiolytic properties as used in traditional medicine.